Pemeriksaan Kesehatan Masyarakat Yapase, Distrik Depapre, Papua - Eva Susanty Simaremare; Septriyanto Dirgantara; Elsye Gunawan; Rani Dewi Pratiwi; Rusnaeni Rusnaeni (JPPM (Jurnal Pengabdian dan Pemberdayaan Masyarakat), 2017)
High blood pressure, diabetes mellitus (DM), uric acid, and cholesterol are disease that can kill patients. The purpose of ths study to support the government in health campaign efforts, especially in Yapase. This study was done by direct examination to participants and education them about health according to their examination result. Examination are blood pressure, glucose, uric acid, and cholesterol levels using GCU (Glocose / Cholesterol / Uric Acid)tTest. This study was held on Thursday 3 August 2017. The location was conducted in Yapase Hall. The number of participants were 32 people. The results show that 13 people (41%) had normal blood pressure, 10 people (31%) had prehypertension, and 9 people (28%) had hypertension. On blood glucose examination 6 people (19%) of the participants had low blood sugar and 26 people (81%) under normal circumstances. On the measurement of blood cholesterol, 2 people (6%) had hypercholesterolemia and 30 people (94%) had normal cholesterol levels under normal conditions. In the measurements of uric acid obtained 3 people (9%) had low uric acid levels, 11 people (34%) had normal uric acid levels and 18 people (56%) had high uric acid levels